Molecular motors and the cytoskeleton. - Vallee, Richard B. (Methods in enzymology, 1998)
This volume attempts to describe the purification and assay of the diverse group of proteins involved in otoplasmic organization. Some of the more promising attempts to apply techniques of molecular biology, genetics, and molecular cytochemistry to these proteins are discussed.